Aboriginal historical archaeological site, Kanyanyapilla camp, McLaren Vale, South Australia. Issue 2 (4th May 2019) - Walshe, Keryn; Malone, Gavin; Telfer, Karl; Gully, Grant
Abstract: Removal of olive trees along a closed public road at McLaren Vale inadvertently revealed a scatter of archaeological material. Subsequent investigation resulted in the identification of an Aboriginal historical camp site. The abundant worked glass associated with the site, and our analysis published here, provides evidence for intensive occupation from the late 1800s to the late 1940s, with overall site use spanning the1860s to1960s. This site, Kanyanyapilla camp (field site no. K50PoC1), provides the first detailed archaeological evidence from the greater Adelaide region of resistance by Aboriginal people against institutional inducement onto missions. Instead, a camp was established away from the immediate township now known as McLaren Vale and the occupants engaged in a range of economic activities in the region. Indeed, Aboriginal people occupying this camp site were engaged in 'hybrid economies' as well as utilising traditional practices, all of which defies the standard notion that Aboriginal people during the latter half of the 19th Century were induced, and later forced, onto missions. That some Aboriginal people may have avoided missions and instead retained a sense of autonomy outside the mission/government inspired nexus of welfare dependency now finds archaeological resonance in South Australia.